ANALISIS PERBANDINGAN LINK BUDGET UNTUK MENGHITUNG PATH LOSS PADA DAERAH URBAN DAN SUBURBAN MENGGUNAKAN METODE OKUMURA HATTA - Dwi Puji Astuti; Lela Nur pulaela (Politeknik Harapan Bersama Tegal, 2023)
As time goes by, the development of cellular communication technology is increasing, this is related to the increasing need for cellular communication. Cellular communication propagation media uses air, propagation between sender and receiver can cause propagation losses and affect the quality of communication. Therefore we need a communication network planning. In wireless communication planning requires link budget calculation. The link budget calculation is useful for cost efficiency and building a quality communication system. Therefore, in this study, link budget calculations in urban and sub-urban areas were made using the Okumara Hatta method and simulations using Matlab software. In this study using data from various sources. The data is used to calculate the path loss value and the received power level. From the results of research using the Okumara-Hatta method, it proves that the greater the distance or distance of the MS (mobile station) to the BTS (Base Transceiver Station), the greater the path loss experienced. The carrier frequency, BTS height, and MS height also affect the starting point of the path loss.